Mapping the risk management landscape: a bibliometric and practitioner-validated thematic analysis - Setyawan, Hendri; Zakaria, Nor Balkish; Ason, Yvonne Joseph; Musa, Kazi; Mohamed Izwan, Iylia Dayana (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2025)
This study offered an integrated bibliometric and thematic analysis to map the intellectual and practical landscape of risk disclosure research. Drawing from literature in Scopus and Web of Science, the study applied co-citation, keyword co-occurrence, and content analysis to explore trends, citation dynamics, emerging themes, author networks, and regional research distributions. Seven major thematic clusters were identified: (1) board characteristics and risk disclosure readability, (2) regulation, climate risk disclosure, and firm value, (3) cybersecurity risk and integrated reporting, (4) institutional investors and enterprise risk management (ERM), (5) financial instruments, compliance, and value relevance, (6) risk disclosure, firm performance, and cost of capital, and (7) ownership structure and corporate governance. To enrich the analysis, insights from two practitioners—an enterprise risk officer and a compliance manager from IDX-listed firms— were incorporated through semi-structured interviews. Their perspectives validated key bibliometric themes and added practical depth. The results highlighted evolving priorities in risk disclosure, shifting from regulatory compliance toward value-relevant, stakeholder-driven narratives. This study offers critical implications for researchers, practitioners, and regulators seeking to enhance transparency, accountability, and decision-making in corporate risk communication.